Open-label, single-arm, single-center clinical study on the effectiveness and safety of a moisturizer containing tocotrienol-rich composition in children with mild to moderate atopic dermatitis - Kang, Nien How; Hon, Weng Chang; Oi, Ming Lai (Wiley, 2023)
Background Little is known about antioxidant efficacy of topical vitamin E on atopic dermatitis (AD) due to lack of controlled clinical studies.